Perspective of Parents of Online Learning in Pandemic Covid-19 - Ida Ayu Hani Erlina; Dwi Santoso; Sigit Apriyanto (Journal of Research in Business, Economics, and Education, 2020)
This study discusses parental perceptions in online learning that took place during the current Covid-19 pandemic. The method used by the researcher is qualitative research, and the data is taken through a questionnaire through the WhatsApp group and random interviews. So that the results obtained by parents' perceptions of online learning today are the lack of understanding of the material that the teacher provides to explain back to their children.